Udruženost PPARG rs3856806 C>T polimorfizma sa indeksom telesne mase, glikemijom na tašte i lipidnim parametrima u srpskih adolescenata - Vidovic, Vanja; Maksimovic, Nela; Vidovic, Stojko; Damnjanovic, Tatjana; Novakovic, Ivana (Scripta Medica, 2021)
Background/Aim: Peroxisome proliferator-activated receptor gamma (PPARγ) belongs to a family of nuclear hormone receptors and ligand-activated transcription factors. PPARG gene is expressed in many tissues including adipose tissue where it plays a crucial role in differentiation of adipocyte, insulin resistance, blood glucose levels and lipid metabolism. The aim of the study was to examine the association of rs3856806 polymorphism with the body mass index (BMI), fasting glucose levels and lipid parameters in Serbian adolescents. Methods: This research included 287 adolescents of both genders (143 boys and 144 girls), 14-15 years of age. Genotype detection was done by polymerase chain reaction-restriction fragment length polymorphism (RFLP) assay. Results: Results showed statistically significant difference in terms of fasting glucose levels among girls (p = 0.013) depending on their genotype. Female carriers of CC genotype had significantly higher level of fasting glucose levels. Also, results showed that in the group of overweight and obese girls, carriers of CT or TT genotype had statistically significant lower values of HDL cholesterol compared to girls - carriers of CC genotype (p = 0.000). However, this result was not confirmed by multiple regression analysis. Statistically significant association of rs3856806 polymorphism was not observed with BMI nor with other lipid parameters. Conclusion: This polymorphism is associated with fasting glucose level and HDL cholesterol among girls. To draw definite conclusions, further research should be conducted including non-genetic factors and other polymorphisms among this gene.